So Volcanoes Created the Dinosaurs? A Quantitative Characterization of the Early Evolution of Terrestrial Pan-Aves - Langer, Max Cardoso; Godoy, Pedro L. (Frontiers in Earth Science, 2022)
The early Mesozoic is marked by several global-scale environmental events, including the emplacement of large igneous provinces, such as the Siberian Traps, Wrangellia, and CAMP. These have been hypothesised as drivers of the successful diversification of Pan-Aves, the lineage of archosaurs closer to birds than to crocodiles. We characterize here the diversification and body size evolution of terrestrial pan-avians (excluding pterosaurs) along the Triassic and Early Jurassic, using phylogenetic- and occurrence-based approaches, in an attempt to test the influence of such drivers. As diversity metrics, we quantified raw species richness and phylogenetic diversity (using time-calibrated phylogenetic trees), and net diversification rates were estimated with PyRate and the episodic fossilized-birth-death model. We have also characterised through-time patterns of body size (femoral length) and estimated body size evolutionary rates. Our results indicate that macroevolutionary shifts estimated from occurrence data are placed more recently in time than those from phylogenetic-based approaches, as shown by the higher diversity increase, diversification rates, and body size disparity of terrestrial Pan-Aves in the Carnian. This is consistent with hypotheses suggesting that the Carnian Pluvial Episode (CPE) was crucial for the early radiation of the group. Yet, phylogeny-based results show higher diversity/diversification rates for the Ladinian and Norian, suggesting a minor effect for the CPE. We also found no meaningful shifts in diversity, diversification, or size-related metrics across the Triassic-Jurassic boundary. Even if the end-Triassic mass extinction possibly emptied ecospace, allowing dinosaur diversity to increase during the Jurassic, our results suggest that this expansion did not occur fast and homogeneously for the entire group. In fact, a sustained reduction in diversity and sub-zero net diversification rates are seen after the extinction, but macroevolutionary patterns here should be interpreted with care towards the end of the Early Jurassic, as they may be biased by an “edge effect”. Overall, few macroevolutionary shifts were consistently identified across all results, suggesting that the early diversification of terrestrial pan-avians was more nuanced and complex than anticipated.